Regulatory roles of RNA binding proteins in the nervous system of C. elegans - Sharifnia, Panid; Jin, Yishi (Frontiers in Molecular Neuroscience, 2015)
Neurons have evolved to employ many factors involved in the regulation of RNA processing due to their complex cellular compartments. RNA binding proteins (RBPs) are key regulators in transcription, translation, and RNA degradation. Increasing studies have shown that regulatory RNA processing is critical for the establishment, functionality, and maintenance of neural circuits. Recent advances in high-throughput transcriptomics have rapidly expanded our knowledge of the landscape of RNA world, but also raised the challenge for mechanistic dissection of the specific roles of RBPs in complex tissues such as the nervous system. The C. elegans genome encodes many RBPs conserved throughout evolution. The rich analytic tools in molecular genetics and simple neural anatomy of C. elegans offer advantages to define functions of genes in vivo at the level of a single cell. Notably, the discovery of microRNAs has had transformative effects to the understanding of neuronal development, circuit plasticity, and neurological diseases. Here we review recent studies unraveling diverse roles of RBPs in the development, function, and plasticity of C. elegans nervous system. We first summarize the general technologies for studying RBPs in C. elegans. We then focus on the roles of several RBPs that control gene- and cell-type specific production of neuronal transcripts.